Modern view on chronic fatigue syndrome and approaches to physical rehabilitation - Grygus, Igor; Yevtukh, Mykola (Journal of Education, Health and Sport, 2018)
Chronic fatigue syndrome is a disease with insufficiently studied hitherto etiology and pathogenesis. Purpose: based on the analysis of literature to form a modern understanding of the syndrome of chronic fatigue and approaches to physical rehabilitation. Methods of the research: analysis of scientific literature, synthesis and generalization. Results: A perspective on the evaluation of the pathogenesis of the disease and the development of new treatments is the view on chronic fatigue syndrome as a pronounced disadapted syndrome, against which the effects of viral infection and immune system disorders are manifested. In the study of predisposing to the development of chronic fatigue syndrome factors, along with high stress, social and economic instability, pollution of the environment, very important are the low standard of living, poor quality and expensive (not available) medical assistance. For patients with chronic fatigue syndrome, compulsory daily walks, therapeutic gymnastics courses, massage, hydrotherapy and autogenous training are recommended. Essential role belongs to complex sanatorium treatment (sparing-training regime of motor activity, diet, internal use of drinking mineral water, mineral baths) and physiotherapy methods. Conclusions: The provision of medical care for patients with chronic fatigue syndrome should begin with early detection of the symptom complex and further readaptation and rehabilitation. The main principle of treatment and rehabilitation of chronic fatigue syndrome is its complexity.